Preliminary report on the research of the JU Institute of Archeology and the AGH UST Faculty of Geo-Data Science, Geodesy, and Environmental Engineering at the Dajaniya and Tuwaneh sites in Jordan – seasons 2018-2019 - Bodzek, Jarosław; Kopij, Kamil; Miszk, Łukasz; Ćwiąkała, Paweł; Puniach, Edyta; Kajzer, Małgorzata; Jellonek, Szymon; Ochałek, Agnieszka; Mrocheń, Dawid; Głowacka, Agata; et al. (Acta Archaeologica Lodziensia, 2022)
The article presents the preliminary results of research conducted by the expedition of the Institute of Archeology of the Jagiellonian University and the Faculty of Geo-Data Science, Geodesy, and Environmental Engineering in the south-western Jordan at the of Dajaniya (Ma’an Husseiniyeh) and Tuwaneh (Tafila Hessa) sites in 2018-2019. The main aim of the research was to create plans for both sites and document the state of preservation of architectural remains using photogrammetry (both pole- and kite-based) as well as terrestrial laser scanning. Additionally, robber pits were recorded at both sites. A surface prospection was also conducted, collecting ceramic and metal materials, which, in the case of Tuwaneh, covered the central part of the site (the area around the socalled caravanserai) and part of the robber trenches and their waste piles. In 2019, three trial trenches were also excavated in the vicinity of the ancient baths at Tuwaneh.